An algorithm for two-player repeated games with perfect monitoring - Dilip Abreu; Yuliy Sannikov (Theoretical Economics, 2014)
Consider repeated two-player games with perfect monitoring and discounting. We provide an algorithm that computes the set V* of payoff pairs of all pure-strategy subgame perfect equilibria with public randomization. The algorithm provides significant efficiency gains over the existing implementations of the algorithm from Abreu, Pearce and Stacchetti (1990). These efficiency gains arise from a better understanding of the manner in which extreme points of the equilibrium payoff set are generated. An important theoretical implication of our algorithm is that the set of extreme points E of V* is finite. Indeed, |E| ≤ 3|A|, where A is the set of action profiles of the stage game.
Keywords: C63; C72; C73; 330; Repeated games; perfect monitoring; computation